CARACTERIZACIÓN DE LA COMUNIDAD DE MALEZAS Y SU DIVERSIDAD EN EL CULTIVO DE BANANO (Musa acuminata) EN TRES ZONAS DEL TRÓPICO ECUATORIANO - Castillo Piloso, Gladys Magenka (2023)
Banana cultivation, faces significant challenges due to weeds. These not only reduce production, but also complicate essential tasks in the crop, such as fertilization, weeding and disease management. The objective of this study was to characterize the weed community and its diversity in three areas of the Ecuadorian tropics: Valencia, Buena Fe and Quevedo. The results revealed different patterns in biological diversity indices at the level of weed families and in similarity comparisons between locations.